Twenty-first century drama the first decade - Courtney, Angela 1967-.; Gale Group (Detroit Gale Cengage Learning, 2012)
Provides first or unique coverage of both domestic and international works of drama from the first decade of the 21st century, featuring in-depth information on around 175 plays and musicals first produced between the years 2000 and 2009.
Front Cover; Half Title Page; Title Page;Copyright Page; Contents; Volume 1 Contents by Title;Editorial Board;List of Contributors;Preface;10 Days on Earth;The 25th Annual Putnam County Spelling Bee;365 Days/365 Plays;36 Views;The 39 Steps;52 Degrees South;Additional Particulars;The Adventures of a Black Girl in Search of God;Afterimage;Age of Arousal;Agokwe;The Alice Trilogy; Altyd Jonker;And Did Those Feet;Anita Bryant Died for Your Sins;Anna in the Tropics;Another Home Invasion;August: Osage County;Avenue Q;Batavia;Behzti (Dishonour;Belfast Blues;Betrayed;Bigger than Jesus;Billy Elliot: The Musical;Blackbird;Black Watch;Blood.Claat;The Blue Light;Blue/Orange;Bone Cage;Born Bad;Breakfast with Mugabe;Breathing in;Brothers in Blood;Building Jerusalem;Burning;The Carnivores;Caroline, or Change; Carthage Must Be Destroyed;Cast Iron;Caught Red Handed;China Doll; Circle Mirror Transformation;The Clean House;Cloudstreet;Clubland;The Coast of Utopia;Cock; Copper Thunderbird;Curfew;Cut Flowers;?Da Kink in My Hair;Damascus;The Dark Things; Dead City; The December Man (L'homme de Décembre);Democracy;A Disappearing Number;Doubt: A Parable;East of Berlin; Eclipsed;Eden;Einstein's Gift;Elizabeth Rex;Elmina's Kitchen;Enron;Exits and Entrances; Fabulation: or, The Re-Education of Undine;Familiar;Far Away;The Far Side of the Moon;Fela!; Flesh Wound; The Force of Change;Four Places;Free Outgoing;From These Green Heights;A Gift for Mom; Girl in the Goldfish Bowl; The Goat, or Who Is Sylvia?;God of Carnage;Grace;Habitat;Hairspray; Half Life; Harbour;Harvest;Heaven;Heroes;The History Boys;Holding the Man;Holy Day;Homebody/Kabul;How to Disappear Completely and Never Be Found;Humble Boy;I Am My Own Wife;In a World Created by a Drunken God;In Flagrante Gothico;Inheritance;In on It;The Intelligent Design of Jenny Chow: An Instant Message with Excitable Music;In the Heights.
Electronic reproduction.
Keywords: English drama -- 21st century -- History and criticism; Theater -- English-speaking countries -- History -- 21st century; Electronic books